A Bibliometric Review of Collaborative Learning: Trends and Future Directions - Judijanto, Loso (The Eastasouth Journal of Learning and Educations, 2025)
This bibliometric study analyzes the trends and dynamics within the field of collaborative learning from 2000 to 2025, focusing on the evolution of research themes, technological integration, and international collaboration networks. Using data sourced exclusively from Scopus, we conducted a detailed review of the literature, examining publication patterns, keyword frequency, and authorship networks. The findings highlight a significant shift towards integrating digital technologies such as AI, machine learning, and gamification in educational practices. Additionally, the study reveals the formation of robust global collaboration networks, indicating a trend towards international partnerships in research. The results underscore the growing importance of interdisciplinary approaches and technological advancements in shaping the future directions of collaborative learning. The study provides valuable insights for educators, researchers, and policymakers aiming to leverage collaborative learning strategies to enhance educational outcomes and student engagement in an increasingly digital world.